A causal link between circulating leukocytes and three major urologic cancers: a mendelian randomization investigation - Zhi-gang, Yi; Han-dong, Wang (Frontiers in Genetics, 2024)
Purpose: This study aimed to explore the influence of serum leukocytes on urologic cancers (UC) using observation-based investigations. In the present study, Mendelian randomization (MR) was employed to assess the link between leukocyte count (LC) and the risk of UC development. Methods: Five LC and three major UC patient prognoses were obtained for MR analysis from genome-wide association studies (GWAS). Furthermore, in order to evaluate reverse causality, bidirectional studies were conducted. Finally, a sensitivity analysis using multiple methods was carried out. Results: There was no significant correlation found in the genetic assessment of differential LC between the co-occurrence of bladder cancer (BCA) and renal cell carcinoma (RCC). Conversely, an individual 1-standard deviation (SD) rise in neutrophil count was strongly linked to a 9.3% elevation in prostate cancer (PCA) risk ([odd ratio]OR=1.093, 95%[confidence interval]CI=0.864-1.383, P=0.002). Reverse MR analysis suggested that PCA was unlikely to cause changes in neutrophil count. Additional sensitivity studies revealed that the outcomes of all MR evaluations were similar, and there was no horizontal pleiotropy. Primary MR analysis using inverse-variance weighted (IVW) revealed that differential lymphocyte count significantly influenced RCC risk (OR=1.162, 95%CI= 0.918–1.470, P=0.001). Moreover, altered basophil count also affected BCA risk (OR=1.249, 95% CI=0.904–1.725, P=0.018). Nonetheless, these causal associations were not significant in the sensitivity analysis. Conclusion: In summary, the results revealed that increased neutrophil counts represent a significant PCA risk factor. The current research indicates a significant relationship between immune cell activity and the cause of UC.